MEANINGS INTERPRETATION IN THE 2010 DOO-WOPS & HOOLIGANS BRUNO MARS’ SONG ALBUM - Rahmadhani, Fachreza; Natsir, M.; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2019)
Songs could have impacts on the community. When Bruno Mars launched his first album the "Doo-Wops & Hooligans" in 2010, it became famous. It was, therefore, the intention of this piece of writing to find out about his fame from his song lyrics in an album. Compared to most Americans who tend to prefer jazz music to pop, Bruno Mars’ style is a mixture of hip-hop and reggae. This study focused on the Bruno Mars’ song lyrics that had been written on the album "Doo-Wops & Hooligans". Findings of the study revealed that most of the song lyrics were dominated by hyperbole indicating that the writer used a lot of exaggeration in his lyrics. Conclusions revealed that most of song lyrics describe a man-to-woman romantic relationship. Lagu-lagu bisa berdampak pada komunitas. Ketika Bruno Mars meluncurkan album pertamanya "Doo-Wops & Hooligans" pada 2010, itu menjadi terkenal. Karena itu, maksud dari tulisan ini adalah untuk mencari tahu tentang ketenarannya dari lirik lagunya di sebuah album. Dibandingkan dengan kebanyakan orang Amerika yang cenderung lebih suka musik pop daripada pop, gaya Bruno Mars adalah campuran antara hip-hop dan reggae. Penelitian ini berfokus pada lirik lagu Bruno Mars yang telah ditulis di album "Doo-Wops & Hooligans". Temuan dari penelitian ini mengungkapkan bahwa sebagian besar lirik lagu didominasi oleh hiperbola yang menunjukkan bahwa penulis menggunakan banyak berlebihan dalam liriknya. Kesimpulan mengungkapkan bahwa sebagian besar lirik lagu menggambarkan hubungan romantis pria-wanita.